Mamma, ho perso la cicogna! (Dialogo intorno all’inesistente diritto contro l’esistenza) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The wife teaches Bioethics, the husband is a lawyer: a couple debates about artificial conception, pre?implantation genetic diagnosis and reflects upon the nature of embryos and the “rights” of the mother. A dialogue in fiction, based on considerations, real cases and judgements (quoted in the text): an original point of view on a delicate issue.
Keywords: abortion; artificial conception; embryo; preâ€implantation genetic diagnosis; rights of the mother